RADIOCARBON INVESTIGATION OF TWO OLD ELMS FROM ROMANIA - PATRUT, Adrian; PATRUT, Roxana T.; BOCOS-BINTINTAN, Victor; RATIU, Ileana-Andreea; RAKOSY, Laszlo; ZDROB, George; VANCA, Eufrosina; VON REDEN, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The paper reports the AMS (accelerator mass spectrometry) radiocarbon investigation results of two superlative elms from Romana, the very large field elm of Calafat, with a wood volume of 85 m3, and the wych elm of Sadova. Two wood samples were extracted from each elm and were analysed by AMS radiocarbon. The oldest dated sample from the elm of Calafat had a radiocarbon date of 350 ± 19 BP, which corresponds to a calibrated age of 415 ± 25 years, while the oldest sample from the elm of Sadova had a radiocarbon date of 188 ± 24 BP, corresponding to a calibrated age of 260 ± 25 years. These values indicate high ages for the two elms, namely 430 ± 25 years or the elm of Calafat and 400 ± 25 years for the elm of Sadova.